2016
DOI: 10.3846/13923730.2014.914079
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Eco-Efficiency Analysis of Highways: A Data Envelopment Analysis

Abstract: Abstract.To ensure the large network of highways is performing sustainably, there is a dire need to quantify sustainability for highways. In this paper, data envelopment analysis (DEA) based mathematical model is developed to evaluate sustainability in an attempt to aid these efforts. Sustainability goals pertaining to the three dimensions of sustainability, social, economic and environmental, were utilized. Utilizing the developed model, sustainability scores of thirty highway sections were calculated and ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Furthermore, Kucukvar et al [116] and Kucukvar et al [117] used a TBL-LCA EIO framework to evaluate economic impacts. Tatari et al [122] used an approach based on the expansion of economic opportunity and the increased value of transportation assets achieved as a consequence of the improvement of road-based transport of goods and the quality maintenance of the roads [122].…”
Section: Environmental Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Kucukvar et al [116] and Kucukvar et al [117] used a TBL-LCA EIO framework to evaluate economic impacts. Tatari et al [122] used an approach based on the expansion of economic opportunity and the increased value of transportation assets achieved as a consequence of the improvement of road-based transport of goods and the quality maintenance of the roads [122].…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…For instance, Alam et al [103] suggested the calculation of the NPV and the Cost-Benefit Ratio (CBR), although in their case study, only NPV was determined. Tatari et al [122] used the Truck Throughput Efficiency (TTE) and the Pavement Condition Score (APC). Kucukvar et al [116] and Kucukvar et al [117] used the Gross Operating Surplus (GOS), Import, and Tax as indicators in their TBL-LCA EIO framework.…”
Section: Environmental Dimensionmentioning
confidence: 99%
“…In the operational dimension (B), the literature discusses sustainability regarding how the road operation can be made more environmentally and socially friendly. First, traffic pollutants-such as GHGs, NO x , SO x , traffic noise, and vibration-should be sufficiently mitigated (e.g., Kokoli, Chassiakos, & Theodorakopoulos, 2007;Tatari, Egilmez, & Kurmapu, 2016;Tatari & Kurmapu, 2011). Second, sustainability is advanced as ensuring safe and secure mobility for all by, for example, minimizing accident risks and reducing the social costs of these risks (e.g., Litman, 2007).…”
Section: Infrastructure Perspective (I)mentioning
confidence: 99%
“…Although eco-efficiency might guide a practical solution for SD, eco-efficiency analyses do not guarantee sustainability because they cover only economic and environmental dimensions (Bruni et al 2011;Charmondusit et al 2014). A broadened eco-efficiency analysis that incorporates the social dimension was recently recommended to thoroughly achieve SD core concepts via benchmarking (Tatari et al 2016;Caiado et al 2017;Nissi and Sarra 2018).…”
Section: Introductionmentioning
confidence: 99%